The fellowship of the ring - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973.; HarperCollins (London : HarperCollins, 2007)
Frodo Baggins, a young hobbit, sets out on a perilous journey to the Cracks of Doom, along with a band of warriors from different kingdoms, to destroy the Dark Lord's Ring of Power.
May include a fold-out color map.
Young Adult
Keywords: Baggins, Frodo (Fictitious character) -- Fiction; Good and evil -- Fiction; Middle Earth (Imaginary place) -- Fiction; Adventure fiction; Baggins, Frodo (Fictional character) -- Fiction; Chinese language; Fantastic fiction